Design of Symmetric Magnetic Lenses with Optimum Operational Conditions - Faiz Abd Alghane, Basma; K. Ahmad, Ahmad (Al-Nahrain Journal of Science, 2021)
In the present paper, the geometrical and optical object properties of symmetrical magnetic lens are designed and analyzed using the electron optical design (EOD) program. The effect of the axial aperture diameter (D), the air gap between the poles (s), the thickness of the poles (t), the excitation parameter NI of the lens are all studied for the best optical properties like the object focal length fo, the spherical and chromatic aberrations coefficients (Cs and Cc respectively). It was found that the optical properties of the object significantly improved with a decrease in the axial aperture diameter and width of the air gap of this lens.    Upon our study, it was found that the best properties are achieved when the air gap width (S=2 mm), and the axial hole diameter (D=6 mm). The effect of the electrode face thickness on the magnetic properties of the proposed magnetic lens is studied, it was found that the best magnetic properties and the highest value of magnetic flux and the lowest value of the axial magnetic field strength bandwidth were at electrode face thickness equal to (3 and 4 mm). Therefore, the best magnetic lens in our design with the best optical properties was S=2 mm, D=6 mm and t=3 mm.